Protection against tuberculosis by passive transfer with T-cell clones recognizing mycobacterial heat-shock protein 65. - Silva, C L (1994)
We have previously shown that mice vaccinated by injection with J774 macrophage-like tumour cells that expressed Mycobacterium leprae heat-shock protein (hsp) 65 as a transgene had acquired a remarkably high degree of protection against subsequent challenge with virulent M. tuberculosis. We show here that antigen-specific T cells cloned from spleens of such vaccinated animals can transfer a high level of protection to non-vaccinated recipients. The most efficient cells were of T-cell receptor (TCR) alpha beta+ and CD4- CD8+ type and specifically lysed mycobacteria-infected macrophages. These findings are consistent with the importance for protective immunity of engaging the endogenous antigen-presenting pathway to bias the immune response towards a cytolytic action against a mycobacterial antigen that is expressed at the surface of infected macrophages. TCR gamma delta+ and TCR alpha beta+ cells interacted synergistically.